2021
DOI: 10.1080/24748668.2021.1885838
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and influence of the underwater phase of breaststroke on short-course 50 and 100m performance

Abstract: The aim was to analyse the influence of the breaststroke underwater phase on 50 and 100m performance. A total of 108 performances in 50m (61 males and 47 females), and 126 performances in 100m (71 males and 55 females) were recorded during the 2019 Short-course National Spanish Championship. The underwater swimming time, distance and velocity were analyzed after the start and turns. Pearson correlation coefficients (r) and regression analysis were applied to compute the relation between the variables. The rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…In short-course races, the contribution of acyclic phases, i.e., start and turns, to the total race time is widely known [16,29,30]. For instance, turn times contributed 32.92 ± 1.09% to total race time in long-course 200 m races [13] compared to 50.84 ± 0.28% in 200 m shortcourse races [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In short-course races, the contribution of acyclic phases, i.e., start and turns, to the total race time is widely known [16,29,30]. For instance, turn times contributed 32.92 ± 1.09% to total race time in long-course 200 m races [13] compared to 50.84 ± 0.28% in 200 m shortcourse races [16].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the timing of the wall approach seems a more important determining factor for race time than wall exit parameters. Some studies investigating key performance indicators of turn performance found velocity during the underwater phase more relevant than underwater time or distance [30,35]. Swimmers attain the highest velocities directly following push-off from the pool wall [34,36].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been recently demonstrated the importance of the start in sprint swimming events. 32,33 The fastest swimming speed by elite swimmers was achieved at the 20 m mark. 2 Our data showed the same trend, although the fastest swimming speed was achieved at the 15 m mark.…”
Section: Curve Fittingmentioning
confidence: 99%
“…Our data showed that the underwater speed (related to the underwater phase) was the variable that presented the most considerable effect in both race distances, but significant only in the 50 m freestyle. Studies indicated that in 100 m events, swimmers reaching faster underwater speeds had a meaningful advantage on swimming start, and consequently on the final race times (Olstad et al, 2020;Sánchez et al, 2021). Other studies focused on understanding the undulatory swimming (Wadrzyk et al, 2021) or the transition from the underwater phase to surface swim (Stosic et al, 2021;Trinidad et al, 2020).…”
Section: Prediction Of the Start Main Outcome (15 M Mark Time) In Each Race (50 M And 100 M Freestyle) And Its Relationship With Other Stmentioning
confidence: 99%